Quantitative analysis of specific labelled RNA'S using DNA covalently linked to diazobenzyloxymethyl-paper. - Stark, G R (1979)
Substantial amounts of DNA (at least 25 microgram per cm2) can be stably bound to diazobenzyloxymethyl (DBM)-paper. Complementary RNA will hybridize to the DNA paper almost completely in 24 hours. Using several different conditions of hybridization and washing, the background of RNA bound non-specifically is very low (between 0.01 and 0.02%) and the efficiency of hybridization is very high (75 to 50% of complementary RNA is bound and retained through the washing procedure). Because the DNA is bound to the paper convalently, it is retained through all the washing and elution steps, and the DNA papers can be re-used many times.